It is time to develop ecological thresholds of toxicological concern to assist environmental hazard assessment. (30th October 2015) - Belanger, Scott E.; Sanderson, Hans; Embry, Michelle R.; Coady, Katie; DeZwart, Dick; Farr, Brianna A.; Gutsell, Steve; Halder, Marlies; Sternberg, Robin; Wilson, Peter
Abstract: The threshold of toxicological concern (TTC) concept is well established for assessing human safety of food‐contact substances and has been reapplied for a variety of endpoints, including carcinogenicity, teratogenicity, and reproductive toxicity. The TTC establishes an exposure level for chemicals below which no appreciable risk to human health or the environment is expected, based on a de minimis value for toxicity identified for many chemicals. Threshold of toxicological concern approaches have benefits for screening‐level risk assessments, including the potential for rapid decision‐making, fully utilizing existing knowledge, reasonable conservativeness for chemicals used in lower volumes (low production volume chemicals (e.g., < 1 t/yr), and reduction or elimination of unnecessary animal tests. Higher production volume chemicals (>1 t/yr) would in principle always require specific information because of the presumed higher exposure potential. The TTC approach has found particular favor in the assessment of chemicals used in cosmetics and personal care products, as well as other chemicals traditionally used in low volumes. Use of the TTC in environmental safety is just beginning, and initial attempts are being published. Key questions focus on hazard extrapolation of diverse taxa across trophic levels, importance of mode of action, and whether safe concentrations for ecosystems estimated from acute or chronic toxicity data are equally useful and in what contexts. The present study provides an overview of the theoretical basis for developing an ecological (eco)‐TTC, with an initial exploration of chemical assessment and boundary conditions for use. An international collaboration under the International Life Sciences Institute Health and Environmental Sciences Institute has been established to address challenges related to developing and applying useful eco‐TTC concepts. Environ Toxicol Chem 2015;34:2864–2869. © 2015 SETAC